Features of manifestation of self-trained athletes specialized in jumping - Liashenko V.N.; Tumanova V.N.; Mariskina T.V. (Fizičeskoe Vospitanie Studentov, 2012)
Analyze different approaches to the formation and self-determination of the individual and the structure of a value judgment, the foundation of which is to assess the world around us. There are three kinds of value judgment: look at the world, look at yourself and look at yourself and the situation in general through the eyes of the third. It is examined the levels of self-manifestation at the qualified athletes, specializing in athletic jumps. The contingent of 30 athletes were tested-athletes of different skill levels between the ages of 17 to 32 years. Self-esteem has 5.5% of the surveyed athletes at the Master of Sports. Overpriced - 38.5% of the athletes. Of them - 10% of the MSIC, 10% and 13.5% of MS CCM. The rest of the respondents athletes who are - 61%, there is a tendency to inflate self-esteem. Determined that the self-assessment is necessary in order to better know their strengths and weaknesses, and use them in their struggle for achieving the goals.